Объяснение:
все показано на рисунке
{Х=у-3
{2х-5у= - 21
2(у-3)-5у= - 21
2у-6-5у= - 21
-3у= - 21+6
-3у= - 15
У=5
Х=5-3=2
ответ : (2;5)
1,5х+у=5 у=5-1,5х
2х-3у=11
2х-3(5-1,5х)=11
2х-15+4,5х=11
6,5х=11+15
6,5х=26
Х=4
У=5-1,5×4=5-6= - 1
ответ :(4;-1)
Объяснение:
все показано на рисунке
Объяснение:
{Х=у-3
{2х-5у= - 21
2(у-3)-5у= - 21
2у-6-5у= - 21
-3у= - 21+6
-3у= - 15
У=5
Х=5-3=2
ответ : (2;5)
1,5х+у=5 у=5-1,5х
2х-3у=11
2х-3(5-1,5х)=11
2х-15+4,5х=11
6,5х=11+15
6,5х=26
Х=4
У=5-1,5×4=5-6= - 1
ответ :(4;-1)